In vitro growth of human keratinocytes and oral cancer cells into microtissues: an aerosol-based microencapsulation technique - Leong, Wai Yean; Soon, Chin Fhong; Wong, Soon Chuan; Tee, Kian Sek; Cheong, Sok Ching; Gan, Siew Hua; Youseffi, Mansour (Multidisciplinary Digital Publishing Institute, 2017)
Cells encapsulation is a micro-technology widely applied in cell and tissue research, tissue transplantation, and regenerative medicine. In this paper, we proposed a growth of microtissue model for the human keratinocytes (HaCaT) cell line and an oral squamous cell carcinoma (OSCC) cell line (ORL-48) based on a simple aerosol microencapsulation technique. At an extrusion rate of 20 µL/min and air flow rate of 0.3 L/min programmed in the aerosol system, HaCaT and ORL-48 cells in alginate microcapsules were encapsulated in microcapsules with a diameter ranging from 200 to 300 µm. Both cell lines were successfully grown into microtissues in the microcapsules of alginate within 16 days of culture. The microtissues were characterized by using a live/dead cell viability assay, field emission-scanning electron microscopy (FE-SEM), fluorescence staining, and cell re-plating experiments. The microtissues of both cell types were viable after being extracted from the alginate membrane using alginate lyase. However, the microtissues of HaCaT and ORL-48 demonstrated differences in both nucleus size and morphology. The microtissues with re-associated cells in spheroids are potentially useful as a cell model for pharmacological studies.